Pathological and Clinical Pathological Changes Induced by Four-week, Repeated-dose, Oral Administration of the Wood Preservative Chromated Copper Arsenate in Wistar Rats. (April 2018) - Takahashi, Naofumi; Yoshida, Toshinori; Kojima, Sayuri; Yamaguchi, Satoru; Ohtsuka, Ryoichi; Takeda, Makio; Kosaka, Tadashi; Harada, Takanori
Chromated copper arsenate (CCA) is used as a wood preservative worldwide. Exposure to it may adversely affect human health. Some events have increased human exposure to CCA, including the Great East Japan Earthquake, which generated a large amount of lumber debris from CCA-treated woods. We elucidated the toxicity due to daily exposure to CCA over a 4-week period at doses of 0, 8, 40, and 80 mg/kg/day in Wistar Hannover rats. Chromium (Cr) and arsenic (As), but not copper, were detected in the plasma samples of rats treated with various doses of CCA. Males and females showed sedation, and males had poor body weight gain. The clinical pathologies observed in both sexes included hypochromic and microcytic anemia, hepatic and renal dysfunction, and changes in lipid and glucose levels. Histopathologically, males and females showed forestomach hyperkeratosis, mucosal epithelial hyperplasia in the small intestine, rectal goblet cell hypertrophy, and lipofuscin deposition in the proximal renal tubule. Females showed diffuse hepatocellular hypertrophy with increased 8-hydroxydeoxyguanosine levels. These results indicated that oral administration of CCA mainly affected hematopoietic, gastrointestinal, hepatic, and renal systems owing to the toxic effects of As and/or Cr. Major toxic effects were observed in both sexes receiving 40 and 80 mg/kg/day.